2021
DOI: 10.1021/acs.analchem.1c02401
|View full text |Cite
|
Sign up to set email alerts
|

Probing N-Heterocyclic Carbene Surfaces with Laser Desorption Ionization Mass Spectrometry

Abstract: The proliferation of N-heterocyclic carbene (NHC) self-assembled monolayers (SAMs) on gold surfaces stems from their exceptional stability compared to conventional thiol-SAMs. The prospect of biological applications for NHC-SAMs on gold shows the need for biocompatible techniques (e.g., large biomolecule detection and high throughput) that assesses SAM molecular composition. Herein, we demonstrate that laser desorption ionization mass spectrometry (LDI-MS) is a powerful and facile probe of NHC surface chemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…3, middle). 52 Most notably, treatment of AuNPs with ( 1 )AgBr gives predominantly [( 1 ) 2 Au] + at 601 m / z (Fig. 3, bottom).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…3, middle). 52 Most notably, treatment of AuNPs with ( 1 )AgBr gives predominantly [( 1 ) 2 Au] + at 601 m / z (Fig. 3, bottom).…”
Section: Resultsmentioning
confidence: 98%
“…LDI-MS characterization is a powerful tool to probe the chemical composition of NHC monolayers and reveal reactions at the surface. 52 Here, we use LDI-MS to probe the ligand transfer process. SERS is a highly surface sensitive technique capable of measuring the vibrational spectroscopy of ligands on AuNP surfaces.…”
Section: Methodsmentioning
confidence: 99%
“…These post-synthetic modifications of NHC–AuNPs have been explored by Camden and Jenkins using SERS 67 and laser desorption ionization mass spectrometry (LDI-MS). 108 A nitro-functionalized NHC–Au( i ) complex was appended to AuNPs and reduced in situ to yield amine-functionalized NHC–AuNPs followed by an in situ amide coupling with benzoic acid.…”
Section: Discussionmentioning
confidence: 99%
“…This high ion yield likely arises from the formation of chemically stable, positively charged, bis‐NHC ions [16a, 19] during the desorption/ionization process [20] . Critically, previous research from our groups with deuterium isotopologues of NHC ligands demonstrated that bis‐NHC gold ions form via desorption of two neighboring ligands and not from a plume chemistry process of the LDI [20] . The high yield of a variety of bis‐NHC gold ions from our NHC‐AuNP library highlights the modularity of a NHC mass barcode library with predictable, easily analyzed mass spectra.…”
Section: Resultsmentioning
confidence: 99%